2017
DOI: 10.17660/actahortic.2017.1156.97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylene on postharvest strawberry fruit tissue biochemistry

Abstract: The effect of continuous ethylene supplementation (50 µL L-1) on cold-stored strawberry fruit physiology and biochemistry, including phytohormones (abscisic acid) metabolism was investigated. In comparison with control fruit which exhibited high sucrose and malic acid contents during storage, ethylene-treated fruits showed increased respiration, sucrose hydrolysis and concomitant reducing sugars accumulation. Ethylene supplementation did not have any effect on phenolic profile. ABA biosynthesis, in both flesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Previous studies that used ethylene elicitors or inhibitors have suggested that exogenous ethylene affects some important quality attributes in strawberry fruit, including firmness (Jiang et al, 2001;Villarreal et al, 2008;Villarreal et al, 2009;Villarreal et al, 2016;Elmi et al, 2017), anthocyanin accumulation and phenylalanine ammonia lyase (PAL) activity (Villarreal et al, 2009;Villarreal et al, 2010;Merchante et al, 2013;Sun et al, 2013;Lopes et al, 2015), phenolic compound accumulation (Villarreal et al, 2010;Lopes et al, 2015), organic acids (Merchante et al, 2013;Lopes et al, 2015;Elmi et al, 2017), sugars (Villarreal et al, 2010;Villarreal et al, 2016;Tosetti et al, 2020) and volatile-related genes (Merchante et al, 2013). However, most of these studies have been conducted with immature strawberry fruit following detachment from the plant, which may alter fruit physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that used ethylene elicitors or inhibitors have suggested that exogenous ethylene affects some important quality attributes in strawberry fruit, including firmness (Jiang et al, 2001;Villarreal et al, 2008;Villarreal et al, 2009;Villarreal et al, 2016;Elmi et al, 2017), anthocyanin accumulation and phenylalanine ammonia lyase (PAL) activity (Villarreal et al, 2009;Villarreal et al, 2010;Merchante et al, 2013;Sun et al, 2013;Lopes et al, 2015), phenolic compound accumulation (Villarreal et al, 2010;Lopes et al, 2015), organic acids (Merchante et al, 2013;Lopes et al, 2015;Elmi et al, 2017), sugars (Villarreal et al, 2010;Villarreal et al, 2016;Tosetti et al, 2020) and volatile-related genes (Merchante et al, 2013). However, most of these studies have been conducted with immature strawberry fruit following detachment from the plant, which may alter fruit physiology.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, when the fruit were harvested at earlier maturity stages and treated with exogenous ethylene, there was a rapidly increase in ethylene production and respiration rate. In addition, strawberries, which are non-climacteric, exhibit high respiration rates after the exposure to exogenous ethylene (Elmi et al, 2017). These studies suggest that exogenous ethylene can influence climacteric and non-climacteric fruit in different ways, possibly because there are ethylene dependent and independent metabolic pathways leading to ripening on each fruit species (Lelièvre et al, 1997;Chen et al, 2020).…”
Section: Respiration Rate and Ethylene Synthesismentioning
confidence: 84%
“…In climacteric fruit, ethylene increases chlorophyllase activity (Shemer et al, 2008), as well as carotenoid synthesis that accelerates color changes from green to yellow, as observed in papaya and mango (Montalvo et al, 2007;Façanha et al, 2019). In non-climacteric fruit, ethylene can also play an important role on reducing green color by increasing chlorophyll degradation, as observed in citrus and pineapple (Goldschmidt, 1997;Paul et al, 2012), as well as on triggering the synthesis of other pigments such as anthocyanins in strawberries (Villarreal et al, 2010;Elmi et al, 2017). Our results suggest that chlorophyll breakdown and synthesis of red/yellow pigments in acerola fruit were ethylene independent processes.…”
Section: Skin Color H Abmentioning
confidence: 99%
“…Rise in respiration rate of tomatoes was observed by Karacali (1990) as noticed in our study. Boe & Salunkhe (1967) in tomatoes and Elmi et al (2017) in strawberries reported that the ethylene treatment increased the rate of CO2 production. However, their outcome contradicted with cluster type tomatoes where control treatment had higher CO2 production than ethylene treated tomatoes.…”
Section: Respiration Ratementioning
confidence: 99%